Pengaruh Lingkungan Kerja, Kepemimpinan, Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan Bank di Batam - Ferdianto, Renndy; Farid, Ridhayati (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
Banking has many employees due to assisting operations in achieving the goals and targets that have been set. However, unfortunately sometimes these goals and targets are not met due to several reasons, one of which is the work environment, leadership, organizational culture and motivation. The aim of the research is to find out employee performance is influenced by the work environment, leadership, organizational culture and motivation. Employee performance is very much needed in the company in achieving company goals. The research method used was explanatory quantitative, a data collection system using a questionnaire distribution technique with a sample of 320 respondents. Data analysis techniques use SPSS. 25 with several tests carried out on data quality, classical assumptions, and hypotheses. The research results show that there is a significant influence of the work environment on employee performance, leadership has a significant influence on employee performance, organizational culture has no significant influence on employee performance, and motivation has a significant influence on employee performance. Finally, from the simultaneous testing, there was a simultaneous influence of the work environment, leadership, organizational culture and motivation on the performance of Bank employees in Batam.